Use of biocompatible xenograft for the surgical treatment of feline corneal sequestrum after lamellar keratectomy - LIAPIS (Ι. Κ. ΛΙΑΠΗΣ) C. I. (Journal of the Hellenic Veterinary Medical Society, 2017)
A Persian cat was referred to our clinic for evaluation of a black plaque located on the cornea of the right eye noticed by the owner three months prior to presentation. Reported clinical signs included ocular discomfort with blepharospasm and epiphora.The diagnosis of corneal sequestrum was made. Due to morphology, chronicity and severity of the symptoms, the cat was treated surgically with lamellar keratectomy followed by covering of the defect with a porcine small intestine derived xenograft. The excellent result was in accordance with the previously reported cases.